1986
DOI: 10.1258/002367786780808695
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of streptozotocin-induced diabetic DBA/2N and CD-1 mice

Abstract: SummaryHistopathological examinations were carried out on femaie DBA/2N and CD·l mice which were autopsied 4 and 12 weeks after six daily intraperitoneal injections of streptozotocin (SZ). Histopathological changes related to SZ treatment were found in the pancreas, liver and kidneys. Little difference was observed between the two strains in the histological changes of the pancreas (a decrease in size of the islets, and degranulation and a decrease in the number of B cells) and liver (hypertrophy of hepatocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…The hepatic changes may be due to the hypertrophy of hepatocytes by an increase in the intracytoplasmic eosinophilic granules. [36] Polyherbal formulation and glibenclamide treatment to the animals reduced the severity of the histopathologic changes caused by STZ.…”
Section: Discussionmentioning
confidence: 99%
“…The hepatic changes may be due to the hypertrophy of hepatocytes by an increase in the intracytoplasmic eosinophilic granules. [36] Polyherbal formulation and glibenclamide treatment to the animals reduced the severity of the histopathologic changes caused by STZ.…”
Section: Discussionmentioning
confidence: 99%
“…STZ is specifically toxic to the beta cells of the pancreas, reducing the amount of insulin available to the animal; its administration is an established method for inducing insulin-dependent (type 1) diabetes in mice. 10 PAT is particularly well-suited for measuring changes in diabetic vasculature because it can monitor vessel-by-vessel changes in diameter, sO 2 , blood flow speed, and total hemoglobin concentrations.…”
mentioning
confidence: 99%
“…While some researchers developing diabetes in mice using STZ (14,25) noted that the hepatocyte nucleus area increased, some (25,26) reported that the size of the cell increased (hypertrophy). Honjo et al (26) revealed that cytoplasmic invaginations formed in the hepatocyte nucleus. Doi et al (14) reported that the hepatocyte nucleus area in STZ diabetic mice was nearly twice as large as the controls and showed irregular structures.…”
Section: Discussionmentioning
confidence: 99%
“…Watkins et al (17), who examined the livers of STZ diabetic mice at the electron microscopic level, reported swelling in the hepatic sinuses, especially on the first and third days, and a visible enlargement between hepatocyte boundaries. While some researchers developing diabetes in mice using STZ (14,25) noted that the hepatocyte nucleus area increased, some (25,26) reported that the size of the cell increased (hypertrophy). Honjo et al (26) revealed that cytoplasmic invaginations formed in the hepatocyte nucleus.…”
Section: Discussionmentioning
confidence: 99%